ANALISIS BAHAN AJAR KURIKULUM 2013 BERBASIS MULTIPLE INTELLIGENCE KELAS IV - Eva Luthfi Fakhru Ahsani (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2020)
Abstract This study aims to describe the 2013 Curriculum thematic book analysis viewed from the aspect of multiple intelligence. Research conducted includes the type of qualitative research. The method of collecting data in the form of analysis is a literature study (library research) in the book Theme 2 Always Saving Energy kelsa IV Curriculum 2013. The research process is carried out by studying the material, analyzing the suitability of the book with aspects of multiple intelligences, describing the results of the analysis and providing conclusions and suggestions . The results of the thematic book analysis show that the distribution of multiple intelligence aspects is not evenly distributed. This can be seen in Subtheme 1 obtained that the highest intelligence in Interpersonal intelligence 18% and the lowest in 6% extension intelligence, Subthema 2 obtained the highest intelligence in kinesthetic intelligence 19% and the lowest existential intelligence 3%, and Subthema 3 obtained the highest intelligence in kinesthetic intelligence 19 % and lowest existential intelligence 3%. Student intelligence can be maximized by developing learning contained in student books by adding student activities that are not yet fully contained in student books. Student activities can be done in the classroom or outside the classroom.   Abstrak Penelitian ini bertujuan untuk mendeskripsikan analisis buku tematik Kurikulum 2013 dilihat dari aspek kecerdasan majemuk (multiple intelligence). Penelitian yang dilakukan termasuk jenis penelitian kualitatif. Metode pengumpulkan data berupa analisis yang bersifat studi literatur pada buku Tema 2 Selalu Berhemat Energi kelas IV Kurikulum 2013. Proses penelitian ini dilakukan dengan cara mengkaji materi, menganalisis kesesuaian buku dengan aspek kecerdasan majemuk, mendeskripsikan hasil analisis dan memberikan kesimpulan dan saran. Hasil analisis buku tematik bahwa distribusi penyebaran aspek kecedasaran majemuk (multiple intelligence) belum merata. Hal ini terlihat pada subtema 1 diperoleh bahwa kecerdasan tertinggi pada kecerdasan Interpersonal 18% dan terendah pada kecerdasan ekstensial 6%, subtema 2 diperoleh kecerdasan tertinggi pada kecerdasan kinestetik 19% dan terendah kecerdasan eksistensial 3%, dan subtema 3 diperoleh kecerdasan tertinggi pada kecerdasan kinestetik 19% dan terendah kecerdasan eksistensial 3%. Kecerdasan siswa dapat dimaksimalkan dengan mengembangkan pembelajaran yang terdapat di buku siswa yaitu dengan menambahkan kegiatan aktivitas siswa yang belum sepenuhnya terdapat di buku siswa. Aktivitas siswa bisa dilakukan di dalam kelas maupun di luar kelas